Tradisi Metutur Orangtua Sebagai Media Sosialisasi Nilai Sosial pada Anak Di Desa Tenganan Pegringsingan - Wiyasa, I Made Tirta; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
This study aims to describe and analyze the tradition of metutur that can be used as a better medium for socializing social values. This research uses qualitative research with descriptive-explorative type. The theory used in this research is the theory of Socialization from George Herbert Mead. The results of this study indicate that the metutur is a good socialization medium in giving meaning to children's social values. In accordance with Mead's Socialization theory, the metutur tradition can provide a role for children from an early age to be ready to become part of society. The role of the metutur in the closeness of parents to their children is felt by local residents, they think that metutur can also preserve the culture in Tenganan. Metutur is also a good medium as a medium for socializing social values ??in the midst of the modern era that has instant social media. Keywords: Tradition, Metutur, Socialization Media, Social Values.